2021
DOI: 10.1126/scitranslmed.aba8146
|View full text |Cite
|
Sign up to set email alerts
|

Redefining IL11 as a regeneration-limiting hepatotoxin and therapeutic target in acetaminophen-induced liver injury

Abstract: Acetaminophen (N-acetyl-p-aminophenol; APAP) toxicity is a common cause of liver damage. In the mouse model of APAP-induced liver injury (AILI), interleukin 11 (IL11) is highly up-regulated and administration of recombinant human IL11 (rhIL11) has been shown to be protective. Here, we demonstrate that the beneficial effect of rhIL11 in the mouse model of AILI is due to its inhibition of endogenous mouse IL11 activity. Our results show that species-matched IL11 behaves like a hepatotoxin. IL11 secreted from APA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(79 citation statements)
references
References 51 publications
8
63
0
Order By: Relevance
“…It was surprising to observe differences in skull morphology and bone phenotypes between Il11 − / − and that published, and replicated by us, for Il11ra1 − / − genotypes, both maintained on C57BL/6J backgrounds. This said, it was recently shown that Ccl27 expression may be disrupted at the Il11ra1 locus in Il11ra1 − / − mice 19 although this is unrelated to the craniosynostosis phenotypes seen in humans with bi-allelic IL11RA LOF mutations. The fact that Il11 − / − mice do not have snout deformities implies that this is unrelated to the loss of IL11 signaling per se.…”
Section: Discussionmentioning
confidence: 99%
“…It was surprising to observe differences in skull morphology and bone phenotypes between Il11 − / − and that published, and replicated by us, for Il11ra1 − / − genotypes, both maintained on C57BL/6J backgrounds. This said, it was recently shown that Ccl27 expression may be disrupted at the Il11ra1 locus in Il11ra1 − / − mice 19 although this is unrelated to the craniosynostosis phenotypes seen in humans with bi-allelic IL11RA LOF mutations. The fact that Il11 − / − mice do not have snout deformities implies that this is unrelated to the loss of IL11 signaling per se.…”
Section: Discussionmentioning
confidence: 99%
“…To study the functional relevance of TGFβ1-or IL11-induced ERK and/or STAT3 activation, we stimulated HCFs with TGFβ1 in the presence of neutralizing IL11 or IL11RA antibodies that were developed to inhibit fibroblast activation (in vitro) and fibrosis phenotypes (in vivo), agnostic of the underlying pathways (Widjaja et al, 2019;Widjaja et al, 2021). In TGFβ1-stimulated HCFs, inhibition of IL11 signaling using either anti-IL11 or anti-IL11RA prevented ERK phosphorylation (at the 24 h time point) but had no effect on STAT3 activity (Figure 1C).…”
Section: Fibrogenesis Is Associated With Il11-induced Erk But Not Stat3 Activationmentioning
confidence: 99%
“…In the same line of evidence, therapeutic blocking NOX1/4 with GKT137831 ameliorated cholestatic fibrosis in Mdr2−/− mice [172]. Furthermore, GKT137831 treatment also prevented liver inflammation after CCl 4 injection [124] and protected from GSH depletion, caspase-3 cleavage and hepatocyte death in acetaminophen-induced liver injury [173]. In a phase 2 clinical trial, GKT137831 was found to be safe and well tolerated (https://clinicaltrials.gov/ct2/show/NCT02010242, accessed on 7 July 2021).…”
Section: Nox Inhibitors As Therapeutic Tools In Liver Diseasesmentioning
confidence: 73%